Incidence of Irritant Contact Dermatitis in Pottery Craftsmen at Sandi Pattalassang Pottery Center, Takalar Regency, Indonesia - Fitria Syahruna (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Backgrounds: Dermatitis is a big problem in public health because this disease is considered common by sufferers. This study aims to analyze the factors that influence the incidence of irritant contact dermatitis in pottery craftsmen at the Sandi Pattallassang Pottery Center, Takalar Regency in 2021. Methods: This research is an analytical study with a cross-sectional study approach. The population in this study was pottery craftsmen. The number of samples in this study was 117 respondents. The sampling technique in this research is using a non-probability sampling method, namely Purposive Sampling. Univariate, bivariate and multivariate analyzes were performed using SPSS 20.0. Results: Factors found to have an effect on the incidence of irritant contact dermatitis in pottery craftsmen at the Pattallassang Pottery Center, Takalar Regency, were working period (ρ value = 0.021), history of skin disease (ρ value = 0.000), personal hygiene (ρ value = 0.048). Meanwhile, those that had no effect on the incidence of irritant contact dermatitis were the length of contact (ρ value = 0.781), history of atopy (ρ value = 0.214), and use of PPE (ρ value = 0.849). The variable of service period is the most influential variable on the incidence of irritant contact dermatitis in pottery craftsmen at the Sandi Pattallassang Pottery Center, Takalar Regency with an Odds Ratio (EXP(B)) value of 0.153. Conclusions: Factors that influence the incidence of irritant contact dermatitis in pottery craftsmen are years of service, history of skin diseases, and personal hygiene, while those that have no effect are the length of contact, history of atopy, and use of PPE, while the most influential variable is years of service. Suggestions in this study are for pottery craftsmen to always pay attention to personal hygiene and the use of PPE in order to avoid irritant contact dermatitis in the workplace.